Postsecondary Planning Perspectives of Black Parents of Young Adults With High-Incidence Disabilities - Erin Pearce Kilpatrick; Jolie Ziomek-Daigle
Informed by disability critical race theory (DisCrit), this phenomenological study explored the perspectives of Black parents of young adults with high-incidence disabilities regarding their experiences with their children's postsecondary planning processes. Fourteen Black parents participated in semistructured interviews and shared recommendations for educator practices. Five overarching themes emerged from the phenomenological data analysis. Namely, Black parents (a) experienced invisibility by a lack of inclusive postsecondary planning, (b) felt marginalized due to collusive forces of ableism and racism, (c) persevered through postsecondary planning processes and beyond, (d) navigated inequities through social supports and other supports, and (e) enacted ongoing resistance and advocacy. Findings illuminate how Black parents experienced their child's postsecondary planning, and we provide recommendations for educators to advance the postsecondary planning needs of multiple marginalized students and their parents.